Continuous optical chlorophyll-a and turbidity data along RV SONNE cruise SO307 - Oelker, Julia; Pontiller, Benjamin; Engel, Anja; Karnatz, Josefine; Pöhnl, Denise; Winguth, Clara; Koberwein, Nathalie; Flerus, Ruth; Klüver, Tania (PANGAEA, 2025)
Underway optical chlorophyll-a and turbidity data were collected along the cruise track with Sea-Bird Scientific ECO FLNTU sensors installed within two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). The SMBs measure alternatingly. While one box is measuring, the other one is being cleaned. The boxes switched generally every 12 hours. The water inlet for the SMBs is at about 4 m below sea surface. Observed chlorophyll-a and turbidity data were both quality controlled. Analysis of the chlorophyll-a and turbidity data during parallel operation of the sensors in the two boxes showed significant differences between the sensors. The sensors were aligned resulting in consistent chlorophyll-a and turbidity time series. The corrected chlorophyll-a data was calibrated based on chlorophyll-a values from discrete water samples taken from the CTD rosette Niskin bottles at depths between 9 and 14 m and measured fluorometrically in the lab. A homogenous upper layer was assumed. Only eight data pairs were used for the calibration which is therefore not expected to be very accurate. The calibrated chlorophyll-a time series and corrected turbidity time series were compared against Globcolour CHL1 and SPM-OC5 products, respectively. Details on all quality control steps and the comparison with satellite data can be found in the data processing report. The data set user should keep in mind that some parts of the time series might be affected by non-photochemical quenching, see data processing report. It was out of the scope of the quality control to flag or correct non-photochemical quenching. The resulting data set contains the original data and corresponding quality flags achieved by the quality control algorithm as well as the calibrated chlorophyll-a and corrected turbidity data with corresponding quality flags. The data source is given through the name of the active SMB. The data set contains data during transit time and station work. We recommend to use ship's speed to filter for only transit data.
Keywords: chlorophyll-a; DAM; Fluorescence; turbidity; Underway measurement